Decaffeination of Coffee Bean Using Fermentation Process: Effect of Starter Concentration and Varieties on The Reduction of Caffeine and Antioxidant Activity - Alwani Hamad; Dwi Nugraheni; Bekti Wulan Sari; Mubshair Naveed (Research in Chemical Engineering, 2023)
Coffee is a popular drink due to its special aroma and taste. Coffee contains caffeine that contributes a distinctive aroma to coffee, which can also be used as a quality parameter. However, if consumed excessively, it can have a negative impact on health. The decaffeination process using fermentation is one of the alternative methods to reduce the caffeine content without altering the characteristic taste and aroma of coffee. The objective of the study was to determine the influence of starter concentration (0-15%) and variety of coffee (Arabica and Robusta) in the decaffeination process using fermentation on reducing caffeine and the antioxidant activity of coffee products. The parameters were investigated regarding the chemical characteristics, including the concentration of caffeine, total flavonoid content (TFC), total phenolic content (TPC), and antioxidant activity tests using the DPPH free radical and FRAP methods. The results showed that the starter concentration and variety of coffee beans had a significant effect on the chemical characteristics (TPC and TFC) and antioxidant activity of decaffeinated coffee (p-value < 0.05). At a starting starter concentration of 5%, caffeine concentration was higher than a starter rate of 1% and did not significantly increase as stater up. Robusta coffee showed a higher decrease in caffeine compared to Arabica coffee.